Reliability of power electronic converter systems - Chung, Henry Shu-hung; Wang, Huai (Professor in energy technology); Blaabjerg, Frede; Pecht, Michael (IET power and energy series, 2016)
This book outlines current research into the scientific modeling, experimentation, and remedial measures for advancing the reliability, availability, system robustness, and maintainability of Power Electronic Converter Systems (PECS) at different levels of complexity.